Modulation of the gut microbiota by metformin improves metabolic profiles in aged obese mice - Lee, Heetae (Gut Microbes, 2018)
The gut microbiota is a contributing factor in obesity-related metabolic disorders. The effect of metformin on the gut microbiota has been reported; however, the relationship between the gut microbiota and the mechanism of action of metformin in elderly individuals is unclear. In this study, the effect of metformin on the gut microbiota was investigated in aged obese mice. The abundance of the genera Akkermansia, Bacteroides, Butyricimonas, and Parabacteroides was significantly increased by metformin in mice fed a high-fat diet. Metformin treatment decreased the expression of IL-1β and IL-6 in epididymal fat, which was correlated with the abundance of various bacterial genera. In addition, both fecal microbiota transplantation from metformin-treated mice and extracellular vesicles of Akkermansia muciniphila improved the body weight and lipid profiles of the mice. Our findings suggest that modulation of the gut microbiota by metformin results in metabolic improvements in aged mice, and that these effects are associated with inflammatory immune responses.